An Axiomatic Approach to the Measurement of Corruption : Theory and Applications - Foster, James E.; Horowitz, Andrew W.; Méndez, Fabio (Oxford University Press on behalf of the World Bank, 2013)
No generally accepted framework exists for constructing and evaluating measures of corruption. This article shows how the axiomatic approach of the poverty and inequality literature can be applied to the measurement of corruption. A conceptual framework for organizing corruption data is developed, and three aggregate corruption measures consistent with axiomatic requirements are proposed. The article also provides guidelines for empirical applications of corruption measures and discusses data requirements. A brief empirical example illustrates how each of the measures captures a distinct view of corruption that yields a different ranking. To the authors' knowledge, this article provides the first analysis of corruption measurement using an axiomatic framework.